Avaliação dos aspectos higiênico-sanitários de um abatedouro público do Rio Grande do Norte - Alencar, Taciana Benevides de (Universidade Federal Rural do Semi-Árido, 2017)
The contamination of meat by pathogenic and deteriorating microorganisms can occur from slaughtering, due to contamination in the premises, to commercialization, posing a risk to the health of consumers. On Thus. This study aimed to evaluate the hygienic-sanitary conditions of a municipal slaughterhouse in Rio Grande do Norte. The hygienic-sanitary conditions of the establishment were observed through a checklist and photographic documentation, as well as the microbiological quality of bovine, porcine, ovine and caprine meat slaughtered at. The hygienic-sanitary conditions were non-compliant in 81.48% of the evaluated parameters. The microbiological quality was satisfactory according to the current legislation, however, high counts of E. coli and Enterobacteriaceae were detected. The public slaughterhouse precarious hygienic-sanitary conditions representing a risk to the public health.
Monografia
Keywords: Qualidade da carne; Abatedouro; Segurança alimentar; Quality of meat; Slaughterhouse; Food safety; CIENCIAS AGRARIAS::MEDICINA VETERINARIA